A Ti-containing nickel hydroxide positive electrode material, a preparation method thereof and application thereof in a nickel-hydrogen battery

CN117154071BActive Publication Date: 2026-10-27CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311109404.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2026-10-27
Estimated Expiration
2043-08-31

AI Technical Summary

Technical Problem

[0005]本发明针对现有镍氢电池用正极材料存在的制约电池高容量发展的技术问题,提供一种含Ti氢氧化亚镍正极材料及其制备方法和在镍氢电池中的应用

Benefits of technology

[0024](1)本发明在α-Ni(OH)2中引入钛元素,由于钛离子的化合价为+4价,复合在α-Ni(OH)2晶粒表面赋予其更多的过剩正电荷,为达到电荷平衡可以吸引更多的阴离子填充到插层间,起到稳定氢氧化亚镍结构的作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117154071B_ABST
    Figure CN117154071B_ABST
Patent Text Reader

Abstract

The application discloses a kind of Ti-containing nickel hydroxide positive electrode material and its preparation method and application in nickel-hydrogen battery, belong to the positive electrode material and its preparation technical field for nickel-hydrogen battery.This application solves the technical problem of existing positive electrode material for nickel-hydrogen battery that restricts the development of high capacity battery.The application uses the method of high-energy ball milling, uses the high-speed movement of grinding ball to impact raw materials uninterruptedly, under certain temperature and pressure conditions, Ti element and nickel hydroxide occur bond and combine together, make Ti element composite to the surface of nickel hydroxide crystal grain, still show the structural characteristics of α-Ni (OH) 2, obtain Ti composite modified α-Ni (OH) 2 positive electrode material.The maximum discharge capacity of the Ti composite modified α-Ni (OH) 2 positive electrode material reaches 380 mAh / g at 1C, and reaches 390 mAh / g at 2C when used as the positive electrode material of nickel-hydrogen battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a Ti-containing nickel hydroxide cathode material, its preparation method, and its application in nickel-metal hydride batteries, belonging to the technical field of cathode materials and their preparation for nickel-metal hydride batteries. Background Technology

[0002] In 1921, the U.S. Patent Office published Edison's invention patent (US1299693), in which Edison changed the positive electrode of the battery to nickel hydroxide. This started people's research on battery positive electrode materials. In recent years, with the proposal of the dual carbon emission reduction goal, new energy, especially the battery field, has received widespread attention. Among them, nickel-metal hydride batteries are currently the best technology solution combining research and development and application in power batteries. Large capacity is even more crucial for the performance of power batteries and is the mainstream trend for future development.

[0003] In published patents (CN 116037918 A, JP 2020-43010A, CN 104600375 A, etc.), researchers have employed various new technologies and methods to improve the overall performance of this type of hydrogen storage alloy. Commonly used methods for optimizing alloy systems include element substitution, preparation of composite alloys, control of alloy composition by adjusting heat treatment regimes, improvement of material properties, and utilization of the common ion effect to improve the distribution of key ions in the electric double layer within the anodic region. In addition, surface treatment of the alloy is also an effective strategy; this method is simple to operate, has low manufacturing costs, and is beneficial for improving the alloy's corrosion resistance and cycle stability in strongly alkaline electrolytes. Currently, the discharge capacity of novel hydrogen storage alloys used as anode materials in Ni-MH batteries has exceeded 400 mAh / g. However, due to the configuration limitations of Ni(OH)2, the capacity of the cathode material is relatively small compared to the anode, which greatly limits the performance of nickel-metal hydride batteries. In published patents (CN 1127163 C, CN116404274A, CN 1235299 C, etc.), BYD in China discovered that adding titanium to traditional β-Ni(OH)2 cathode materials can improve the high-temperature performance of batteries (CN1269615A). However, due to its theoretical capacity of only 289 mAh / g, the cathode of nickel-metal hydride batteries is limited in capacity, while the anode has excessive capacity. Therefore, the bottleneck restricting the high-capacity development of nickel-metal hydride batteries is the capacity of the cathode material.

[0004] Another configuration of nickel hydroxide, α-Ni(OH)₂, has a theoretical discharge capacity of 482 mAh / g. This is because α-Ni(OH)₂ has a larger intercalation distance, which improves the ion transport rate and results in higher charge-discharge efficiency. However, α-Ni(OH)₂ is structurally unstable under strongly alkaline conditions or high temperatures and will spontaneously transform into β-Ni(OH)₂. Furthermore, as a cathode material, the α-Ni(OH)₂ structure collapses during charge-discharge experiments, leading to a decrease in discharge capacity. Therefore, there is relatively little research on its use as a cathode material in published patents. However, this has not prevented researchers from studying its stability. How to stabilize its structure has been a problem that has been a subject of intense research and remains to be solved for over a century. Summary of the Invention

[0005] This invention addresses the technical problems that restrict the development of high-capacity batteries in existing nickel-metal hydride battery cathode materials by providing a Ti-containing nickel hydroxide cathode material, its preparation method, and its application in nickel-metal hydride batteries.

[0006] The technical solution of the present invention:

[0007] One of the objectives of this invention is to provide a Ti-containing nickel hydroxide cathode material, which is a Ti-containing composite modified α-Ni(OH)2 cathode material, wherein the molar ratio of Ti to Ni in α-Ni(OH)2 is 1:(8.2-10.3).

[0008] Further specifying, the molar ratio of Ni in Ti to α-Ni(OH)2 is 1:9.

[0009] Further specifying, the Ti-containing material is metallic titanium powder or TiO2 powder.

[0010] Further specifying, the TiO2 powder is rutile.

[0011] Furthermore, the purity of the titanium powder is specified as 99%.

[0012] The second objective of this invention is to provide a method for preparing the above-mentioned Ti-containing nickel hydroxide cathode material, the method comprising the following steps:

[0013] (1) The Ti-containing material and α-Ni(OH)2 were ball-milled as a composite material;

[0014] (2) After ball milling, the composite material is cleaned with alcohol and dried to obtain Ti-containing nickel hydroxide cathode material.

[0015] Further specifying, (1) the Ti-containing substance is metallic titanium powder or TiO2 powder.

[0016] To further specify, the TiO2 powder is rutile.

[0017] Furthermore, the purity of the metallic titanium powder is 99%.

[0018] Further specifying, the ball milling conditions in (1) are: ball-to-material ratio of (30-50):1, rotation speed of 120-180 r / min, and time of 8-12 h.

[0019] Further specified, the ball-to-material ratio is 40:1, the rotation speed is 160 r / min, and the time is 10 h.

[0020] Furthermore, stainless steel balls are used as grinding balls.

[0021] Further specify the drying conditions as follows: drying temperature 65℃, drying time 6h.

[0022] A third objective of this invention is to provide an application of the above-mentioned Ti-containing nickel hydroxide cathode material, which is used as a cathode material in nickel-metal hydride batteries.

[0023] This invention employs a high-energy ball milling method, utilizing the continuous high-speed impact of grinding balls on the raw material. Under specific temperature and pressure conditions, Ti element bonds with nickel hydroxide, causing Ti to be incorporated into the surface of nickel hydroxide grains while still exhibiting the structural characteristics of α-Ni(OH)2, thus obtaining a Ti-modified α-Ni(OH)2 cathode material. Compared with existing technologies, this invention offers the following advantages:

[0024] (1) In this invention, titanium is introduced into α-Ni(OH)2. Since the oxidation state of titanium ions is +4, the composite on the surface of α-Ni(OH)2 grains gives them more excess positive charge. In order to achieve charge balance, more anions can be attracted to fill the intercalation space, which plays a role in stabilizing the nickel hydroxide structure.

[0025] (2) When the Ti composite modified α-Ni(OH)2 material prepared in this invention is used as a positive electrode material for nickel-metal hydride batteries, the maximum discharge capacity reaches 380 mAh / g at 1C and 390 mAh / g at 2C. It can be seen that the Ti composite modified α-Ni(OH)2 material prepared in this invention has excellent charge and discharge capacity performance and can be widely used as a positive electrode material for nickel-metal hydride batteries, and is suitable for promotion and application. Attached Figure Description

[0026] Figure 1 XRD curves of three cathode materials, α-Ni(OH)2, A+Ti and A+TiO2, prepared in Comparative Example 1, Example 1 and 2; (1) α-Ni(OH)2, (2) A+Ti, (3) A+TiO2;

[0027] Figure 2SEM images and EDS spectra of the A+Ti cathode material prepared in Example 1;

[0028] Figure 3 SEM images and EDS spectra of the A+TiO2 cathode material prepared in Example 2;

[0029] Figure 4 The discharge specific capacity of nickel-metal hydride batteries assembled with the cathode materials prepared in Examples 1 and 2 at different rates;

[0030] Figure 5 Charge-discharge curves of nickel-metal hydride batteries assembled with the cathode materials prepared in Examples 1 and 2 at 1C;

[0031] Figure 6 The XRD patterns of the A+Ti cathode material prepared in Example 1 and the α-Ni(OH)2 cathode material prepared in Comparative Example 1 after multiple charge-discharge cycles are shown. Detailed Implementation

[0032] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0033] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0034] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0035] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0036] XRD testing: The instrument used was a German Bruker D8Advance, using Cu target K-rays, with a test voltage of 40kV, a current of 40mV, a scanning range of 5-80, and a scanning step size of 0.02. Note that the sample surface should be kept flat.

[0037] SEM and EDS tests: A Hitachi S-4800 instrument was used, primarily for analyzing the surface morphology and elemental distribution of the samples. The prepared cathode material powder was ultrasonically dispersed, adhered to the sample stage, and sputter-coated with gold before testing. The scanning current was 10 mA and the voltage was 10 kV. When using an energy dispersive spectroscopy (EDS) instrument for elemental analysis of the sample surface, the operating current was 15 mA and the operating voltage was 20 kV.

[0038] Example 1

[0039] (1) Using α-Ni(OH)2 material synthesized by chemical precipitation as the main material, 200 mesh Ti powder was added. The molar ratio of the amount of Ti powder added to Ni in α-Ni(OH)2 was 1:9. The mixture was loaded into a ball mill jar as a composite raw material. Stainless steel balls of different sizes were used as grinding balls. The ball-to-material ratio was controlled at 40:1. The ball milling was carried out by dry grinding. The ball milling conditions were: the ball mill frequency was controlled at 160 r / min and the ball milling time was 10 h. During the mechanical ball milling process, the high-speed impact of the stainless steel balls caused the temperature of the ball mill jar to rise, and the temperature was about 200 to 300 °C.

[0040] (2) After the ball milling process, the composite material is cleaned with alcohol and dried to obtain Ti composite modified α-Ni(OH)2 cathode material, abbreviated as A+Ti.

[0041] Example 2

[0042] The difference between this embodiment and Embodiment 1 is that rutile TiO2 powder is used instead of Ti powder; the remaining parameter settings and process steps are the same as in Embodiment 1. The specific operation process is as follows:

[0043] (1) Using α-Ni(OH)2 material synthesized by chemical precipitation as the main material, 200 mesh rutile TiO2 powder was added. The molar ratio of Ti to Ni in α-Ni(OH)2 was 1:9. The mixture was loaded into a ball mill jar as a composite raw material. Stainless steel balls of different sizes were used as grinding balls. The ball-to-material ratio was controlled at 40:1. The ball milling was carried out by dry grinding. The ball milling conditions were: the ball mill frequency was controlled at 160 r / min and the ball milling time was 10 h. During the mechanical ball milling process, the high-speed impact of the stainless steel balls caused the temperature of the ball mill jar to rise, which was about 200 to 300 °C.

[0044] (2) After the ball milling process, the composite material is cleaned with alcohol and dried to obtain Ti composite modified α-Ni(OH)2 cathode material, abbreviated as A+TiO2.

[0045] Comparative Example 1

[0046] The α-Ni(OH)2 used in Example 1 was used as the positive electrode material.

[0047] Example of effect

[0048] (1) The three cathode materials prepared in Example 1, Example 2 and Comparative Example 1 were characterized by XRD, and the results are as follows: Figure 1 As shown, by Figure 1 As can be seen, compared with the XRD pattern of α-Ni(OH)2, the two composite materials A+Ti and A+TiO2 still maintain the structure of α-Ni(OH)2, but diffraction peaks of Ti and TiO2 appear respectively, indicating that Ti element is incorporated into the material, but no chemical doping occurs.

[0049] (2) Figure 2 and Figure 3 The images show SEM images and EDS spectra of two composite materials, A+Ti and A+TiO2, respectively. Figure 2 It can be seen that the Ti element in the A+Ti sample is only locally enriched on the surface of the α-Ni(OH)2 grains, while the Ti element in the A+TiO2 sample can be uniformly distributed on the surface of the grains, but it does not penetrate into the grains to play a doping role.

[0050] (3) Charge and discharge performance test

[0051] Battery positive electrode: 20mg of active material (A+Ti and A+TiO2 respectively) is weighed and thoroughly mixed with 500mg of carbonyl nickel powder in a mortar. Then, it is pressed into a 10mm×1mm sheet by maintaining a pressure of 15MPa for 1min on a small tablet press. The sheet is then encapsulated in 20mm×20mm nickel foam and pressed into a single piece on the tablet press. Finally, a nickel strip is fixed to one end of the nickel foam as the positive electrode tab using a spot welding machine.

[0052] Battery negative electrode: Commercially available LaNi5 alloy is used as the active material. 100mg of it is weighed and mixed thoroughly with 500mg of carbonyl nickel powder in an agate mortar. It is then pressed into a disc of the same size as the battery positive electrode and encapsulated in 20mm×20mm foam nickel. The nickel strip is then welded together with a spot welding machine to serve as the negative electrode tab, ensuring that the active material of the negative electrode is in sufficient excess relative to the positive electrode.

[0053] The prepared positive and negative electrode sheets were separated by two layers of separator, and the electrode sheets were wrapped with nickel wire several times and tied tightly. The fixed electrode sheets were immersed in 6M KOH solution for more than 24 hours to ensure that the electrode sheets were fully wetted by the electrolyte. Then, they were assembled into an open half cell for subsequent charge and discharge performance experiments.

[0054] Charge-discharge cycle test: Connect the half-cell that has been soaked for 24 hours to the battery tester. According to the activation regime set by the positive electrode active material, first charge at a current density of 0.2C for 4 hours, then charge at 0.1C for 2 hours. After standing for 15 minutes, start discharging at 0.2C. Set the cutoff voltage to 1.0V to complete one activation. After 3-5 activations, the charge-discharge cycle test can be performed.

[0055] Battery discharge specific capacity was tested at 1C and 2C, with a cutoff voltage of 1.0V. The results are as follows: Figure 4 As shown, by Figure 4 It is evident that the discharge specific capacity of the A+TiO2 composite material is significantly superior to that of the A+Ti sample. The maximum discharge capacity of the A+Ti sample at 1C is only 270 mAh / g, and the rate discharge capacity at 2C is also only 200 mAh / g. This is because the titanium powder only serves to refine the α-Ni(OH)2 material through ball milling, disrupting the layered structure of nickel hydroxide and hindering the transport and diffusion channels of protons and ions, resulting in poor discharge performance of the composite material. In contrast, the maximum discharge capacity of the A+TiO2 composite material reaches 380 mAh / g at 1C and 390 mAh / g at 2C, both significantly better than the A+Ti sample. Kinetic behavior analysis of the two composite materials indicates that the electrochemical reaction of the A+TiO2 composite material is relatively easier due to its lower liquid junction resistance and faster mass diffusion rate.

[0056] When the cathode material prepared in Comparative Example 1 was assembled into a nickel-metal hydride battery and its discharge specific capacity was tested, it was found that the discharge specific capacity began to decrease after 140 cycles, indicating that the α-Ni(OH)2 structure collapsed. Figure 4 It can be observed that A+Ti and A+TiO2 still maintain a stable discharge specific capacity after 150 cycles. Therefore, the introduction of Ti or TiO2 can maintain the structure of α-Ni(OH)2 and increase its cycle count.

[0057] To compare with the performance of batteries at room temperature (25°C), water bath temperatures were set at 40°C and 55°C to test the performance of simulated batteries under different temperature conditions and charge / discharge regimes. At 2C, the discharge capacity was 96% and 89% of that at room temperature, respectively.

[0058] The battery's charge and discharge performance was tested at 1C, and the results are as follows: Figure 5 As shown, by Figure 5It can be seen that after constant current charging for 2000s, the voltage of the A+Ti sample reached 1.52V and remained there until 3600s, while the charging voltage of the A+TiO2 sample gradually increased over time, reaching a final voltage of about 1.5V. From the discharge curve, the discharge voltage of the A+Ti sample remained between 1.25-1.3V within 2000s, and then rapidly decayed to the cutoff voltage of 1.0V. The discharge time of the A+TiO2 sample lasted for about 3300s, which is a significant improvement over the A+Ti sample, indicating that its discharge capacity is also higher.

[0059] Figure 6 The XRD patterns of the A+Ti cathode material prepared in Example 1 and the α-Ni(OH)2 cathode material prepared in Comparative Example 1 after multiple charge-discharge cycles are shown below. Figure 6 It can be seen that the Ti-modified α-Ni(OH)2 material still maintains a good α-Ni(OH)2 structure after multiple charge-discharge cycles, making it more stable and increasing the number of cycles. However, the peak intensity of the α-Ni(OH)2 cathode material prepared in Comparative Example 1 decreases after multiple charge-discharge cycles, indicating that the α-Ni(OH)2 structure collapses.

[0060] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.

Claims

1. A Ti-containing nickel hydroxide cathode material, characterized in that, This material is a Ti-containing composite modified α-Ni(OH)2 cathode material, wherein the molar ratio of Ti to Ni in α-Ni(OH)2 is 1:9; the Ti-containing material is rutile TiO2; By using high-energy ball milling, Ti elements are bonded to nickel hydroxide and combined together, so that Ti elements are incorporated into the surface of nickel hydroxide grains; Ti elements do not penetrate into the interior of the grains.

2. A method for preparing the Ti-containing nickel hydroxide cathode material according to claim 1, characterized in that, include: (1) The Ti-containing material was mixed with α-Ni(OH)2 and ball-milled; (2) After the ball milling process is completed, the material is cleaned and dried to obtain the Ti-containing nickel hydroxide cathode material; (1) The ball milling conditions are: ball-to-material ratio of 30-50:1, rotation speed of 120-180 r / min, and time of 8-12 h; (2) The drying conditions are: drying temperature of 65℃ and drying time of 6 h.

3. The preparation method according to claim 2, characterized in that, Stainless steel balls are used as grinding balls.

4. The application of the Ti-containing nickel hydroxide cathode material according to claim 1, characterized in that, It is used as a positive electrode material in nickel-metal hydride batteries.

Citation Information

Patent Citations

  • High-power wide-temperature-zone power nickel-hydrogen battery

    CN104600375A

  • High-temperature Ni / Hz battery and its manufacture

    CN1127163C

  • Coating method of titanium dioxide coated rare earth hydrogen storage alloy powder for negative electrode of nickel-metal hydride battery

    CN116037918A

  • Nickel-metal hydride battery and preparation method thereof

    CN116404274A

  • Active positive electrode material of composite Ni-H battery and Ni-H power accumulator

    CN1235299C